Effect of Using Plasma Injection in the Treatment of Biceps Femoris Rupture of 110 Contraindications - Baqer, Eftekhar Mutar (International Journal of Psychosocial Rehabilitation, 2020)
--- The aim of study to use plasma injection for athletes with cramp rupture and tendon rupture of the biceps femoris muscle. The hypothesis of the research is the effect of plasma injection on the speed of healing of the muscle biceps femoris torn muscle. The research methodology consisted of using the experimental approach with two equal groups, while the research community represented a hostile 110 contraindications in Najaf. For the biceps femoris muscle and both according to the time of injury as after injury 72 hours is injected with the needles of this needle and once by the doctor and the specialist after the rehabilitation curriculum by a specialist in the rehabilitation team was conducted tests the same conditions for pre-test. The researchers used the statistical program of (SPSS) in extracting their results the most important conclusions reached by the researchers are: Low pain level early.Increase the strength of the biceps muscle at a better level for the experimental group.